Adulteration and filth in spices - Zamboni, Claydes de Quadros (1991)
217 samples of four kinds of spices: 48 of cloves, 55 of anise, 57 of cassia and 57 of cumin acquired in Sao Paulo, Brazil trade, were examined for adulteration and for filth detection, from 1986 to 1989. Microscopical examination showed that 112samples (51,61%) were disagreeing with Brazilian Legislation: 95 (84,82%) were adulterated with starch or with spices of other kinds; 34 (30,35%) contained sand or soil; 10 (8,93%) were adulterated with mycelia filaments and 6 (5,36%) contained insects or mites. Ground spices were more adulterated (30,87%) than whole spices (19,82%) and ground cumin were more adulterated than the others ground spices (52,63%). Whole anise were more adulterated than the others whole spices (65,45%).